How money works the facts visually explained - Sturgeon, Alison; Collins, Allie; Pengelley, Diane; Palffy, Georgina; Dunne, Jemima; Khan, Tash (Dorling Kindersley Limited, 2017)
Get the answers to hundreds of financial questions with How Money Works, including how to invest for the future, how to maximise your income, how financial markets work, and how governments control money. Discover essential know-how on everything from debt management to online fraud, and learn to manage your own money from payments to pensions. This intriguing guide breaks down the jargon of the financial world, with insights into personal, business, and governmental finance, and giving you the definitions to cash flow, bonds, superannuation, the open market, and hundreds more. Fully up-to-date with the latest financial developments, including quantitative easing and cryptocurrencies such as Bitcoin, How Money Works is your indispensable guide to the world of money.